Single-Cell Transcriptome Profiling of Immune Cell Repertoire of the Atlantic Cod Which Naturally Lacks the Major Histocompatibility Class II System - Guslund, Naomi Croft; Solbakken, Monica Hongrø; Brieuc, Marine S. O.; Jentoft, Sissel; Jakobsen, Kjetill S.; Qiao, Shuo-Wang (Frontiers in Immunology, 2020)
The Atlantic cod’s unusual immune system, entirely lacking the Major Histocompatibility class II pathway, has prompted intriguing questions about what mechanisms are used to combat bacterial infections and how immunological memory is generated. By single-cell RNA sequencing we here report an in-depth characterisation of cell types found in immune tissues, the spleen and peripheral blood leukocytes of Atlantic cod. Unbiased transcriptional clustering revealed eleven distinct immune cell signatures. Resolution at the single cell level enabled characterisation of the major cell subsets including the cytotoxic T cells, B cells, erythrocytes, thrombocytes, neutrophils and macrophages. Additionally, to our knowledge we are the first to uncover cell subsets in Atlantic cod which may represent dendritic cells, natural killer-like cells and a population of cytotoxic cells expressing GATA-3, a master transcription factor of T helper 2 cells. We further identify putative gene markers for each cluster and describe the relative proportions of each cell type in the spleen and peripheral blood leukocytes. Of the major hematopoietic cell populations, the lymphocytes make up 55% and 68% of the spleen and peripheral blood leukocytes respectively, while the myeloid cells make up 45% and 32%. By single-cell analysis, this study provides the most detailed molecular and cellular characterisation of the immune system of the Atlantic cod so far.